2015
DOI: 10.14814/phy2.12307
|View full text |Cite
|
Sign up to set email alerts
|

Posttranscriptional regulation of adrenal TH gene expression contributes to the maladaptive responses triggered by insulin-induced recurrent hypoglycemia

Abstract: Acute metabolic stress such as insulin-induced hypoglycemia triggers a counterregulatory response during which the release of catecholamines (epinephrine), the activation of tyrosine hydroxylase (TH) enzyme and subsequent compensatory catecholamine biosynthesis occur in the adrenal medulla. However, recurrent exposure to hypoglycemia (RH), a consequence of tight glycemic control in individuals with type 1 and type 2 diabetes compromises this physiological response. The molecular mechanisms underlying the malad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 54 publications
3
38
0
Order By: Relevance
“…Some researchers have shown diminished response to acute hypoglycaemia after 2 episodes of antecedent hypoglycaemia on the previous day [28, 4244] whereas some have induced 1 episode of antecedent hypoglycaemia per day for 2 to 4 days [3235, 37, 3941, 61] prior to testing the response to subsequent hypoglycaemia (see Table 2). Kudrick et al [38] have tested 1 and 2 antecedent hypoglycaemic episodes a day and reported that the plasma adrenaline response to subsequent hypoglycaemia was significantly reduced only in the rats that had two hypoglycaemic episodes a day, which is contradictory to a number of the abovementioned studies that have successfully achieved a significant reduction in plasma adrenaline response with 1 episode of antecedent hypoglycaemia for 1, 2, or 3 days. In our laboratory, we tested the effects of one or two episodes of antecedent hypoglycaemic episodes per day for two consecutive days on the adrenaline secretion in response to subsequent hypoglycaemia on day 3 (Figure 3).…”
Section: Reproducing the Haaf Phenomenon In Rodentsmentioning
confidence: 94%
See 4 more Smart Citations
“…Some researchers have shown diminished response to acute hypoglycaemia after 2 episodes of antecedent hypoglycaemia on the previous day [28, 4244] whereas some have induced 1 episode of antecedent hypoglycaemia per day for 2 to 4 days [3235, 37, 3941, 61] prior to testing the response to subsequent hypoglycaemia (see Table 2). Kudrick et al [38] have tested 1 and 2 antecedent hypoglycaemic episodes a day and reported that the plasma adrenaline response to subsequent hypoglycaemia was significantly reduced only in the rats that had two hypoglycaemic episodes a day, which is contradictory to a number of the abovementioned studies that have successfully achieved a significant reduction in plasma adrenaline response with 1 episode of antecedent hypoglycaemia for 1, 2, or 3 days. In our laboratory, we tested the effects of one or two episodes of antecedent hypoglycaemic episodes per day for two consecutive days on the adrenaline secretion in response to subsequent hypoglycaemia on day 3 (Figure 3).…”
Section: Reproducing the Haaf Phenomenon In Rodentsmentioning
confidence: 94%
“…However, subcutaneous administration of insulin reportedly produced variable depth and length of hypoglycaemia when compared to i.p administration [33]. A number of studies have performed i.p administration of insulin to induce antecedent hypoglycaemia [30, 33, 34, 38, 61]. Although the most preferred route of administration in many studies is the i.v route [35, 36, 39, 40, 4244] (see Table 2), some researchers have used a combination of i.p and i.v or s.c and i.v with the i.p or s.c injections used to induce antecedent hypoglycaemia and the i.v administration or continuous i.v infusion used to produce the subsequent hypoglycaemic episode [30, 31, 33, 34, 37, 41].…”
Section: Reproducing the Haaf Phenomenon In Rodentsmentioning
confidence: 99%
See 3 more Smart Citations